Shock wave emission and ice breaking effect of multiple interacting bubbles. (15th August 2021) - Cui, Pu; Zhang, A-Man; Wang, Shi-Ping
Abstract: This work investigates the special bubble behavior during multiple-bubble interaction and the resultant damage effect, especially the shock wave and its damage to ice. The work aims to extend the study on the bubble's potential application in ice breaking to multiple-bubble cases. To this end, we generated four in-phase pulsating bubbles by underwater electric discharge beneath an ice plate. The bubble behavior was filmed with a high-speed camera and the shock waves were visualized by a shadowgraph method. Some unique bubble characteristics were shown, including jetting, non-spherical collapsing, splitting and coalescing. Shock waves were also observed to be released from various parts of the collapsing bubble and from liquid-liquid impact. The bubble-bubble and bubble-ice interaction greatly influences the bubbles' morphological evolution which leads to various patterns of shock wave emissions. Therefore, it resulted in different damage potential manifested by ice fracturing. It is shown that the damaging effect of bubbles can be affected by bubble-bubble and bubble-boundary interaction and thus manipulated in such ways when needed. Highlights: Four bubbles interact and collapse with multiple shock wave emissions. Ice can be easily fractured by bubble-induced shock waves. Fracturing is severer due to shock waves reflected from the air-ice interface. Ice breaking capability is related to bubble position and alignment.